Comparative evaluation of efficacy of subgingivally delivered 1.2% Atorvastatin and 1.2% Simvastatin in the treatment of intrabony defects in chronic periodontitis: a randomized controlled trial - Santosh S. Martande; Minal Kumari; A. R. Pradeep; Sonender Pal Singh; Deepak Kumar Suke (Tabriz University of Medical Sciences, 2017)
Background. Statins are the recently evolved agents that aid in periodontal regeneration and ultimately in attaining periodontal health. Atorvastatin (ATV) and Simvastatin (SMV) are specific competitive inhibitors of 3-hydroxy-2-methyl-glutaryl coenzyme A reductase. The current study was conducted to compare the effectiveness of 1.2% ATV and 1.2% SMV, in addition to scaling and root planing (SRP), in the treatment of intrabony defects in subjects with chronic periodon-titis. Methods. Ninety-six individuals were categorized into three treatment groups: SRP plus 1.2% ATV, SRP plus 1.2% SMV and SRP plus placebo. Clinical parameters of full-mouth plaque index (PI), modified sulcus bleeding index (mSBI), probing depth (PD), and relative attachment level (RAL) were recorded at baseline before SRP and at 3, 6 and 9 months. Bone fill was assessed using percentage radiographic defect depth reduction at baseline, 6 months and 9 months. Results. Both ATV and SMV showed significant PD reduction and RAL gain than placebo. ATV group showed greater mean PD reduction and mean RAL gain as compared to SMV group at 3, 6 and 9 months. Furthermore, ATV group sites exhibited a significantly greater percentage of radiographic defect depth reduction (33.23 ± 3.11%; 34.84 ± 3.07%) as compared to SMV (30.39 ± 3.36%; 32.15 ± 3.37%) at 6 and 9 months. Conclusion. ATV resulted in greater improvements in clinical parameters with higher percentage of radiographic defect depth reduction as compared to SMV in the treatment of intrabony defects in CP subjects.